A New Hybrid Organic-Inorganic Chain: [(Phen)Cu-?-(?2 O:O?-Vp2o10h3)2-Cu(Phen)] N - Venegas-Yazigi, D; Venegas-Yazigi, D (2012)
The structure of the title compound, poly[(dihydrogen-phosphato-?O) (?3-hydrogenphosphato)di-?-xido-(1,10-phenanthroline)copper(II) vanadium(V)], [CuV(HPO4)(H2PO4)O 2(C12H8N2)]n , is defined by [(phen)Cu-?-(?2 O:O?-VP2O 10H3)2-Cu(phen)] units (phen is 1,10-phenanthroline), which are connected to neighbouring units through vanadyl bridges. Neighbouring chains have no covalent bonds between them, although they inter-digitate through the phen groups via ?-? inter-actions. © 2012 International Union of Crystallography.